108k views
1 vote
I don't get this pls help

I don't get this pls help-example-1

1 Answer

3 votes

Answer:

d, e

Explanation:

The applicable rules of exponents are ...

(a^b)(a^c) = a^(b+c)

a^-b = 1/a^b

__

In this case, it means the product is ...

(6^1)(6^0)(6^-3) = 6^(1+0-3) = 6^-2 = 1/6^2 = 1/36

__

The 6 without an exponent is equivalent to 6^1, an exponent of 1.

The sum of the exponents is -2.

Add the exponents to simplify the expression.

The value of the expression is 1/36.

An equivalent is any expression that results in 6^-2. One such is (6^5)(6^-7).

__

Only the last two choices, d and e, apply.

User Antimirov
by
5.3k points